Perancangan Dashboard Interaktif Untuk Visualisasi Data Penjualan Menggunakan Teknologi Big Data - Achsan Noorsalam (CV. SINAR HOWUHOWU, 2025)
This study aims to design and develop an effective interactive dashboard for sales data visualization by leveraging big data technology. The ever-increasing volume of data necessitates more sophisticated solutions for business analysis, where static data visualization is no longer adequate. Using a descriptive-evaluative approach, this research designs a system that integrates Apache Spark for large-volume data processing and modern web technologies for the user interface. The result is a dashboard that not only displays key sales metrics in real-time through various charts but also empowers users with interactive features such as filtering and drill-down capabilities. Functionality and performance testing showed that the system could process millions of data rows with low latency. User evaluation confirmed a high level of satisfaction with the ease of use and clarity of the visualizations. This study thus proves that combining big data technology with a user-centered dashboard design can transform complex sales data into valuable business insights, accelerating decision-making and improving operational efficiency.